THE ROLE OF THE MANUFACTURING ON THE INDONESIAN ECONOMY - Aditya Dwi Saputra; Aryani; Salwa Salsabilla; Zalva, Rifana; Aulia Maharani; Rahmad Yanuardi (CV. Era Digital Nusantara, 2023)
This article uses qualitative research methods and literature to collect information from various written sources. This study utilizes secondary data sources, including digital literature such as websites, journals and bulletins, to explore the factors that influence Indonesia’s manufacturing industry and contribute to the country’s economic growth. This research covers both the barriers and drivers of industrial improvement. Investment in the industrial sector plays an important role in economic growth, making it one of the main areas of interest for domestic investors. The industrial sector is considered a significant contributor to development, as evidenced by the steady growth of Indonesia’s GDP from year to year. Thus, it is the main driver of the country’s economic progress.